Mass transfer and kinetic studies on mercury adsorption by titania nanofibers - Dixit, Abhilasha; Mishra, P. K.; Alam, M. S. (EDP Sciences, 2016)
The stringent laws and tight regulation on heavy metal bearing wastewaters being discharged into the water stream lead to emergence of technically advanced and super effective treatment methods. Heavy metal contaminated aqueous streams have become a global concern due to their carcinogenicity and delirious effects on human health. In particular, the health hazards of mercury include adverse effect on central nervous system, pulmonary and kidney functions, etc. Having a maximum discharge limit of 0.001 mg/L, which is the lowest amongst other heavy metals, mercury contamination has become a matter of global concern. In the present study, TiO2 having a proven track record for its affinity for heavy metals was lab synthesized in the form of fiber mats and tested for its adsorptive behaviour towards Hg(II) in aqueous system. The electrospinned nanofibers possessed smooth morphology and very high surface area ≈ 740 m2/g. The batch adsorption experiments showed titania nanofibers possessed great affinity towards Hg(II). At the most optimized conditions the removal percentage went remarkably high to 95.5% with initial Hg(II) concentration of 0.01 mg/L. Since the rate limiting steps in adsorption are of vital importance in order to define the rate parameters for design purposes, the present study takes into account External mass transfer, Weber and Morris and Boyd mass transfer diffusion models for Hg(II) adsorption on lab synthesized titania nanofibers. The equilibrium data were then analyzed using Langmuir, Freundlich and Temkin sorption models and the characteristic sorption parameters for each isotherm were determined. The Mass transfer mechanism appeared to be film diffusion controlled and data fitted best to Freundlich isotherm with regression value of 0.991. The discussion also focuses on few of the recently used adsorbents for Hg(II) uptake and their comparison with the present study on the basis of removal percentage and kinetics involved. Promising adsorbent characteristics and rapid Hg(II) uptake makes this process a convenient one.
Keywords: Adsorbents; Nanofibers; Mass transfer; Titanium dioxide; Mercury (metal)